Evaluation of the neuroprotective potential of benzylidene digoxin 15 against oxidative stress in a neuroinflammation models induced by lipopolysaccharide and on neuronal differentiation of hippocampal neural precursor cells - Gilvânia A. Cordeiro; Jessica A. Faria; Leticia Pavan; Israel J. P. Garcia; Eduarda P. F. I. Neves; Gustavo Fernando de Frazao Lima; Hericles M. Campos; Pâmela Y. Ferreira; Paulo C. Ghedini; Elisa M. Kawamoto; Maira C. Lima; José A. F. P. Villar; et al. (Frontiers in Pharmacology)
Neuroinflammation, often driven by the overproduction of reactive oxygen species (ROS), plays a crucial role in the pathogenesis of neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases. The susceptibility of the brain to oxidative stress is attributed to its high metabolic activity and limited antioxidant defense. This study aimed to evaluate the neuroprotective potential of Benzylidene Digoxin 15 (BD-15) following treatment and pretreatment in a lipopolysaccharide (LPS)-induced neuroinflammation model. Additionally, we examined whether BD-15 enhances the generation of neurons from neural progenitor cells (NPCs).Male Wistar rats were used for acute treatment studies and divided into four groups: control (saline), BD-15 (100 μg/kg), LPS (250 μg/kg), and LPS + BD-15 (250 μg/kg + 100 μg/kg). Swiss albino mice were used for chronic pretreatment studies and divided into the following groups: control (saline), BD-15 (0.56 mg/kg), LPS (1 mg/kg), and LPS + BD-15 (1 mg/kg + 0.56 mg/kg). Behavioral changes were assessed using the open field test, and brain tissues were analyzed for oxidative stress markers, including malondialdehyde (MDA), reduced glutathione (GSH), protein carbonylation, catalase (CAT), superoxide dismutase (SOD), and glutathione S-transferase (GST). To assess neurogenesis, primary NPC cultures derived from the hippocampus of newborn Wistar rats were used, which led to reduced locomotor activity and increased oxidative stress, particularly in the cortex, as indicated by elevated MDA levels and reduced GSH levels. BD-15 treatment reversed these effects, notably by restoring GSH levels and reducing protein carbonylation in the cerebellum. Chronic BD-15 treatment in Swiss mice improved oxidative stress markers including MDA, SOD, CAT, and GST. Furthermore, BD-15 exhibits neuroprotective properties by alleviating oxidative stress and motor dysfunction, suggesting its potential as a therapeutic agent for neuroinflammatory disorders. However, BD-15 did not affect NPC cell proliferation, indicating that this cardiotonic steroid did not alter the cell cycle of these progenitor cells.